If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y = 11y + 3 Reorder the terms: 8y = 3 + 11y Solving 8y = 3 + 11y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-11y' to each side of the equation. 8y + -11y = 3 + 11y + -11y Combine like terms: 8y + -11y = -3y -3y = 3 + 11y + -11y Combine like terms: 11y + -11y = 0 -3y = 3 + 0 -3y = 3 Divide each side by '-3'. y = -1 Simplifying y = -1
| w/11=3 | | 6+2(8f-2)=4(1+f) | | 6.2x-5+x-1.5=0 | | p=180*(33.333/100) | | (-4)-(-.8)=x | | (x^2+6x-4)+(-x^2-6x+4)= | | 91+(-11)= | | 5y^2+y+1y=4 | | 3/x=5/2x | | 8z+33=3(3z+11)-z | | 89=x+13(7) | | 12x^2-(121/12)=0 | | -5(x-3)=10 | | -3(2x+2)=6x-8 | | 69=3(4x-1) | | 4x-1+2x-1=5y | | -5x-19=10 | | 15x+25y=120 | | 1y=3x-3 | | 915=10a-7 | | 5(3)-7=2(3+1) | | 94+27t=715 | | 5x-4(x+2)=29 | | =-4h+5j-4j+7h | | 5(x-3)=14 | | (2x)/7=2x^2 | | 5(2x-4)+7=12+3(2x+1) | | 816=24(v+12) | | 3)x-y)/5(2x/3y) | | -7(1+5x)=7(x+5) | | 120/350 | | 5y^2+4+1y=4 |